Thermal behaviour of fumaric acid, sodium fumarate and its compounds with light trivalent lanthanides in air atmosphere - Ionashiro, E. Y.; Caires, Flavio J. [UNESP]; Siqueira, A. B.; Lima, L. S. [UNESP]; Carvalho, C. T. (Springer, 2012)
Characterization, thermal stability and thermal decomposition of light trivalent lanthanide fumarates, as well as, the thermal behaviour of fumaric acid and its sodium salt were investigated employing simultaneous thermogravimetry and differential thermal analysis, differential scanning calorimetry, Fourier transform infrared spectroscopy (FTIR), TG-FTIR techniques, elemental analysis and complexometry. on heating, sublimation of fumaric acid is observed, while the thermal decomposition of the sodium fumarate occurs with the formation of a mixture of sodium carbonate and carbonaceous residue. The thermal decomposition of light trivalent lanthanide fumarates occurs in consecutive and/or overlapping steps with the formation of the respective oxides: CeO2, Pr6O11, and Ln(2)O(3) (Ln = La, Nd, Sm, Eu, Gd).
Keywords: Fumaric acid; Light lanthanides; Fumarate; Thermal behaviour